Building Political Awareness of Gender for The Young Learners (THUFULA, 2023)
The development of early childhood political and gender learning is based on various comprehensive rational considerations, children are a quality asset of the nation. Its success will determine the sustainability of the nation's life so that every nation in the world develops as well as possible. The purpose of this study was to determine the planning, methods, media, children's learning behavior, inhibiting factors, teacher efforts in overcoming obstacles, as well as evaluations carried out by teachers in introducing politics and gender in children aged 5-6 years in RA Ya Salam, Pati Regency. This study uses a descriptive research method with a qualitative approach. The samples of this study were 2 teachers and 21 children in grade B. The teacher's lesson plans were prepared quite well. There are 4 methods used, namely, habituation, storytelling, conversing and sociodrama. The media used are pictures, books, videos and dolls. The changing learning behavior of children includes children who are able to classify themselves and children understand how to look the right way as a boy and a girl, children become aware of gender equality and are passionate about achieving their goals. The inhibiting factors faced by teachers are the stereotyped behavior of gender roles that have been entrenched, as well as the limited time and learning media. The results of this study indicate that political and gender learning in overall learning has been implemented well.